THE EXPERIENCE OF "MATLAB 6.0"® USE IN THE SIMULATION OF THE PULSE-PHASE CONTROL SYSTEM OF THE THYRISTOR VOLTAGE REGULATOR WITH THE ACTIVE-INDUCTIVE LOAD - Hamzaoui, Abdelaziz; Melikhov, Artem; Tsukanov, Vadim; Kolokolov, Yuriy (International Journal of Computing, 2014)
The paper is dedicated to the realization of the structural model of the pulse-phase control system (PPCS) of the thyristor voltage regulator (TVR) with an active-inductive (RL) load in the medium of "MATLAB 6.0" ® Describing the possibilities of "MATLAB 6.0" ® in the dynamic systems simulation, some problems connected with the use of special instrument means, included in structure of Toolbox Simulink Library, are examined.